Pengaruh Usia, Pendidikan, Keahlian Terhadap Penyerapan Tenaga Kerja Di Kota Medan Menurut Perspektif Islam - Ryan Arianda; Waizul Qarni; Purnama Ramadhani Silalahi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research aims to indetify the influence of age (X1), education (X2), skills (X3) on labor absorption in the city of medan according to an Islamic perspective. The type of research carried out is quantitative, the data source is primary. The methode used to collect data was by distributing questionnaire statements to the people of Medan city using a purposive sampling technique with the criteria of respondents aged 15-64 years, with a sample size of 100 respondents. Then the data obtained was processed using SPSS. The data analysis technique used in this research is instrument testing, classical assumption testing. The results of this research state that the t test shows that age has a significant effect on labor absorption, skills have a significant effect on labor absorption.